2016
DOI: 10.3310/hsdr04100
|View full text |Cite
|
Sign up to set email alerts
|

Preparing for Home: a before-and-after study to investigate the effects of a neonatal discharge package aimed at increasing parental knowledge, understanding and confidence in caring for their preterm infant before and after discharge from hospital

Abstract: BackgroundImproved survival and shorter length of stay (LOS) for preterm infants, together with poorly organised discharge planning in some neonatal units, leaves many parents ill prepared to take their babies home, with increased use of out-of-hours services. Despite the importance accorded to family-orientated neonatal care by the Department of Health and the National Institute for Health and Care Excellence, few neonatal units offer structured, family-orientated discharge planning.ObjectivesTo implement a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
3
0
1
Order By: Relevance
“…36 -39 A structured discharge planning process reduced ED visits and costs in a population of very preterm infants. 40 Although this concept is not novel in the general pediatric setting, there has been a lag between design and implementation in the NICU setting. Leveraging technology such as telemedicine, FaceTime, and other applications might enable NICUs to improve family-centered care and perform discharge teaching in a flexible manner, which is particularly important for low-income families who may face additional barriers to coming to the NICU.…”
Section: Discussionmentioning
confidence: 99%
“…36 -39 A structured discharge planning process reduced ED visits and costs in a population of very preterm infants. 40 Although this concept is not novel in the general pediatric setting, there has been a lag between design and implementation in the NICU setting. Leveraging technology such as telemedicine, FaceTime, and other applications might enable NICUs to improve family-centered care and perform discharge teaching in a flexible manner, which is particularly important for low-income families who may face additional barriers to coming to the NICU.…”
Section: Discussionmentioning
confidence: 99%
“…Discharge planning should begin early and provide incremental education about the discharge process (20). The Train-To-Home program delivers information on neonatal health and key NICU-to-home milestones to increase parental understanding of infant clinical progress and subsequent readiness for discharge (65). Overnight transition rooms also facilitate discharge readiness as parents provide independent care within the monitored environment (66,67).…”
Section: Family-based Nicu Interventionsmentioning
confidence: 99%
“…In an audit of the length of stay (LOS) of preterm infants in local neonatal units (LNUs; as defined by the UK Department of Health) 2 in the Southwest region from 2011 to 2013, we found that almost all infants born at 27–33 weeks’ gestation were discharged home well before their original EDD, with almost 50% being discharged home around 4 weeks before this date. 14 Manktelow also showed that infant LOS varies between neonatal units, so using local data may be helpful. 11 …”
Section: Introductionmentioning
confidence: 99%